The effect of Paraquat Dichloride application on diversity and abundance of soil arthropods in the corn field - Tjandra Anggraeni; T Taufikurahman; M Meilisa; Yeyet Setiawati; Isma Fadilla; Asih Suryati (School of Life Sciences and Technology, Institut Teknologi Bandung, 2020)
We investigated the effect of paraquat dichloride herbicide application on diversity and abundance of soil arthropods in a corn field. In addition to control (0 mL/L), four concentrations of paraquat dichloride were applied i.e. 3.33 mL / L, 4 mL / L, 4.66 mL / L and 5.33 mL / L. Sampling was carried out four times, namely at T0 (before tillage), T1 (after tillage), T2 (after spraying herbicides), and T3 (before harvesting) using a pitfall trap method. Soil arthropod samples were identified to the family level. The total number of individuals was then analyzed to obtain species richness, species dominance index, species diversity index and similarity index of Sorensen. The result showed that paraquat dichloride did not give any significant effect (p>0.05) on the number of individuals, species richness, species dominance index, diversity index and Sorensen similarity index of soil arthropods. The composition of soil arthropods in the control and in the treatment with the highest concentration shows a high level of similarity.